Evaluating Education Cost Indices in Indonesia: A Comparative Analysis of Construction Cost Index and Purchasing Power Parity Using Empirical Methods - Widiputera, Ferdi; Rahayu, Wardani; Suryadi, S (Universitas Muhammadiyah Surakarta, 2024)
This study employs an empirical methodology to investigate the calculation of indices for determining the unit costs of equivalent education. This study compares the Construction Cost Index (CCI) and Purchasing Power Parity (PPP) in order to evaluate their relative effectiveness. A review of the existing literature on these indices reveals a need for more refined calculation and comparison methods. The study employs data from the Indonesian Central Statistics Agency (CSA), including CCI and PPP figures from 2021 and allocations for School Operational Assistance (SOA) for non-formal education in 2022, to examine the relative significance of the CCI and PPP. The findings indicate that the CCI exerts a greater influence than the PPP. Furthermore, the application of a relative importance approach through multiple regression analysis reveals a robust positive correlation between the CCI and PPP, underscoring their intricate interrelationship.